Evaluation of Bio-Hydrogen Production by Dark Fermentation from Cocoa Waste Mucilage (2023)
The problems caused by a large amount of waste produced every day become one of the main concerns of world nations. Then, a question is how various actions arise that seek a transformation in the habits and mentalities. One way to contribute to this cause is to change the sources of polluting energy for sustainable energy, such as hydrogen based. It has a high energy efficiency, and its combustion does not generate polluting emissions. Likewise, as a source for the generation of clean energy, residual biomass is used, which turns out to be a feasible option since its availability is abundant. In the cocoa industry, one of the residues that stands out for its quantity is the cocoa mucilage. This residue can act as a substrate to provide biogas, and that contains high levels of sugars, fibers, proteins, and nutrients. However, in this study, the possibility of producing hydrogen from cocoa mucilage is evaluated by dark fermentation processes. The evaluation is carried out on a laboratory scale, by tests in batch reactors made of 250 ml amber glass and with a 220 ml headspace. The temperatures evaluated during the experiment were 35°C (mesophilic) and 55 C (thermophilic). The organic loads evaluated during the process were 4, 8, and 12 grams of volatile solids per liter (gVS / L), respectively. The experimental testing duration was subject to the presence of methane in the gas produced. For determining the methane presence, a portable analyzer was used. The gas determination was done daily. The evidence of the reaction rate in the tests at 55° C is higher than at 35° C, and the presence of methane at thermophilic conditions occurred at five days, while the mesophilic conditions occurred at 23 days. It is found that, for tests at two temperatures, the best results are detected when the organic load is 12 gVS / L, and the maximum hydrogen production (703 mL H2) is reached when the temperature is 35° C. The maximum production suggests that under mesophilic conditions the process can be maintained in hydrolysis for longer times. Copyright © 2020, AIDIC Servizi S.r.l.